Le Études de la nature (1784) di Bernardin de Saint-Pierre e la poetica leopardiana - Silvestri, Chiara (Rivista Internazionale di Studi Leopardiani, 2021)
The essay highlights the consonances between Saint-Pierre’s Études de la nature and Leopardi’s works, proposing that the mixture of sensibility and sensationalism which inspired the treatise strongly influenced the poet’s attitude to nature. Leopardi’s idyll originated from that mood, which tended to persist, in some respects, in spite of his gradual distancing from the finalism of the Études.